2009
DOI: 10.1080/15265160902985027
|View full text |Cite
|
Sign up to set email alerts
|

The Coming Era of Nanomedicine

Abstract: This essay presents some general background on nanomedicine, particularly focusing on some of the investment that is being made in this emerging field. The bulk of the essay, however, consists of explorations of two areas in which the impacts of nanomedicine are likely to be most significant: diagnostics and medical records and treatment, including surgery and drug delivery. Each discussion includes a survey some of the ethical and social issues that are likely to arise in these applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 16 publications
0
28
0
1
Order By: Relevance
“…99 In addition to general commentaries addressing social and ethical dimensions of nanoscale science and engineering research, 100,101 a growing body of professional literature continues to address potential ethical issues arising specifically from the use of various nanotechnologies in clinical diagnosis and medical treatment. Key issues include the observation that "nanomedicine is likely to be one of the most -if not the most-profitable applications of nanotechnology", 102 and as other commentators have noted, such "extreme profitability" 102 leads to concerns that global equality in access to health care might be even further compromised. 103,104 Rather notably, in 2012, the Journal of Law, Medicine & Ethics published a special issue that featured a number of perspectives from research scientists, bioethicists, and others [105][106][107][108][109][110][111] addressing potential ethical issues in nanomedicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…99 In addition to general commentaries addressing social and ethical dimensions of nanoscale science and engineering research, 100,101 a growing body of professional literature continues to address potential ethical issues arising specifically from the use of various nanotechnologies in clinical diagnosis and medical treatment. Key issues include the observation that "nanomedicine is likely to be one of the most -if not the most-profitable applications of nanotechnology", 102 and as other commentators have noted, such "extreme profitability" 102 leads to concerns that global equality in access to health care might be even further compromised. 103,104 Rather notably, in 2012, the Journal of Law, Medicine & Ethics published a special issue that featured a number of perspectives from research scientists, bioethicists, and others [105][106][107][108][109][110][111] addressing potential ethical issues in nanomedicine.…”
mentioning
confidence: 99%
“…103,104 Rather notably, in 2012, the Journal of Law, Medicine & Ethics published a special issue that featured a number of perspectives from research scientists, bioethicists, and others [105][106][107][108][109][110][111] addressing potential ethical issues in nanomedicine. While there are concerns that "nanomedical interventions present a higher level of uncertainty than do more conventional biomedical interventions" 107 -particularly with regard to clinical trials of nanomedicines in humans -most commentators agree that, fundamentally, there are no "new" ethical concerns specific to medical nanotechnologies 102,105,112 that are not subsumed within existing biomedical ethics guidelines. 113 However, there appears to be broad consensus that the potential scope, extent, and technical complexities of medical nanotechnologies justify further, long-term examination of potential ethical implications.…”
mentioning
confidence: 99%
“…6,14,15 Reports indicated that the market value of nanomedicines in the US was around $53 billion in 2011, with the demand expected to increase by 17% per year to $110 billion in 2016. 7,16 Because of the rapidly growing market demand and the current limited understanding of nanomedicines, it is important that we clarify the physical and chemical characteristics of nanomedicines as well as their effectiveness and functions. 17 Accompanied nanotoxicology concerns require studies that investigate a variety of physicochemical aspects of nanomaterials, International Journal of Nanomedicine 2014:9…”
mentioning
confidence: 99%
“…Being at the same microscopic scale as biological functions allow nanoparticles to interact with many biological processes, this potentially can have an impact in many aspects of the healthcare. The new field of 'Nanomedicine' (Allhoff, 2009) will not meets its immense potential until the safety of nanomaterials is fully demonstrated. It is prudent to investigate any potential adverse effects on health or the environment of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%